Biosynthesis of Sinapigladioside, an Antifungal Isothiocyanate from Burkholderia Symbionts. (4th May 2021) - Dose, Benjamin; Niehs, Sarah P.; Scherlach, Kirstin; Shahda, Sophie; Flórez, Laura V.; Kaltenpoth, Martin; Hertweck, Christian
Abstract: Sinapigladioside is a rare isothiocyanate‐bearing natural product from beetle‐associated bacteria ( Burkholderia gladioli ) that might protect beetle offspring against entomopathogenic fungi. The biosynthetic origin of sinapigladioside has been elusive, and little is known about bacterial isothiocyanate biosynthesis in general. On the basis of stable‐isotope labeling, bioinformatics, and mutagenesis, we identified the sinapigladioside biosynthesis gene cluster in the symbiont and found that an isonitrile synthase plays a key role in the biosynthetic pathway. Genome mining and network analyses indicate that related gene clusters are distributed across various bacterial phyla including producers of both nitriles and isothiocyanates. Our findings support a model for bacterial isothiocyanate biosynthesis by sulfur transfer into isonitrile precursors. Abstract : Alternative pathways : Genetic analyses and labeling studies provide the first insights into the biosynthesis of the rare isothiocyanate natural product sinapigladioside from beetle‐associated bacteria that might protect the beetle offspring against entomopathogenic fungi. Contrary to known isothiocyanate biosynthetic pathways, sinapigladioside assembly involves an isonitrile synthase.